Utilization of Apple Cider Vinegar By-Products Into Zero Waste Based Functional Food Ingredients at CV Sinar Tirta Indonesia - Nurjannah; Miftakhul Cahyati; Dedes Amertaningtyas; Khothibul Umam Al Awwaly; Agus Susilo; Indha Fitria Pangesti; Ahmad Yuda Ihwanudin (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
In Indonesia, apples are one of the types of fruit that are widely cultivated and widely consumed as processed foods, such as apple cider vinegar CV Sinar Tirta Indonesia, a producer of apple cider vinegar, consistently yields apple pulp as a by-product. In addition to apple cider vinegar, the processing process produces apple pulp by-products. Apple pulp by-products, which consist of pulp and skin that has extraordinary nutrition, make it very suitable to be processed into useful food. Innovation is needed so that apple pulp by-products are not only used for animal feed mixtures that have low selling value. To realize the processing of waste-based products, it must be able to change the by-product into a product that has the maximum possible economic value, as shown in this community service activity, namely changing the by-product of apple vinegar into flour and ingredients for making cookies that were attended by the surrounding community, students, employees, and business actors. This training provides direct benefits to participants, namely gaining new knowledge about how to process apple pulp into functional food ingredients. This training proves that processing apple pulp with current technology is easy to do and produces a high-value product.